Clinical outcomes with long-term sorafenib treatment of patients with hepatocellular carcinoma: a multicenter real-life study. (9th August 2018) - Sacco, Rodolfo; Granito, Alessandro; Bargellini, Irene; Zolfino, Teresa; Saitta, Carlo; Marzi, Luca; Tapete, Gherardo; Bresci, Giampaolo; Marinelli, Sara; Tovoli, Francesco; Attardo, Simona; Rossi, Margherita; et al.
Aim: This multicenter field-practice study evaluates outcomes of long-term sorafenib in hepatocellular carcinoma (HCC) patients.Methods: Consecutive HCC patients on sorafenib were enrolled. We evaluated those receiving sorafenib for ≥12 months.Results: Out of 800 patients on sorafenib, 81 (10%) received long-term treatment. Median duration of treatment was 22.7 months (range: 12.3–92.6). Only 21 (26%) reported grade 3/4 adverse events. Complete response was reported in 11 patients (14%). Median overall survival was 34.8 months (95% CI: 29.9–44.3). Only baseline Child–Pugh class was associated with survival.Conclusion: Sorafenib could result in long-term control of HCC in a relevant proportion of patients. Given the availability of regorafenib in the second-line setting, an earlier introduction of systemic therapy may be considered according to clinical indications.